2022
DOI: 10.1155/2022/4873008
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Use of Pigeon Pea for Human and Animal Diets

Abstract: Pigeon pea (PP) [Cajanus cajan (L.) Huth] plays an important role in preserving poor smallholders’ major source of income in the tropics and subtropics by improving food and feed security, particularly protein intake. In the meantime, protein deficiency is frequent in tropical and subtropical regions due to rapidly increasing human populations and the high cost of animal-origin proteins. As a result, pulse crops should be their primary source of protein. Among these, PP is the most important pulse crop utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…As summarized in Table 1, pigeon pea is rich in carbohydrates (19.46–62.68 g/100 g), proteins (16.76–29.26 g/100 g), and fat (1.08–5.31 g/100 g), as well as crude fibers (1.20–8.63 g/100 g) (Adamu & Oyetunde, 2013; Ade‐Omowaye et al., 2015; Adenekan et al., 2018; Akubor, 2017; Amarteifio et al., 2002; Athanas, 2022; Choi et al., 2020; Rizvi et al., 2022). Moreover, pigeon pea is sufficient in essential amino acids, including leucine (0.2–0.6 g/100 g), lysine (0.3–1.5 g/100 g), valine (0.2–1.1 g/100 g), isoleucine (0.2–0.8 g/100 g), histidine (0.1–0.8 g/100 g), threonine (0.2–0.8 g/100 g), methionine (0.02–0.3 g/100 g), tryptophan (0.04–0.6 g/100 g), and phenylalanine (0.4–8.7 g/100 g) (Adenekan et al., 2018; Athanas, 2022; Kuraz Abebe, 2022). The high level of leucine and lysine makes pigeon pea especially suitable for people with obesity, diabetes mellitus (Pedroso et al., 2015), and people who need more calcium such as athletes (Chromiak & Antonio, 2002).…”
Section: Nutritional Profile Of Pigeon Peamentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in Table 1, pigeon pea is rich in carbohydrates (19.46–62.68 g/100 g), proteins (16.76–29.26 g/100 g), and fat (1.08–5.31 g/100 g), as well as crude fibers (1.20–8.63 g/100 g) (Adamu & Oyetunde, 2013; Ade‐Omowaye et al., 2015; Adenekan et al., 2018; Akubor, 2017; Amarteifio et al., 2002; Athanas, 2022; Choi et al., 2020; Rizvi et al., 2022). Moreover, pigeon pea is sufficient in essential amino acids, including leucine (0.2–0.6 g/100 g), lysine (0.3–1.5 g/100 g), valine (0.2–1.1 g/100 g), isoleucine (0.2–0.8 g/100 g), histidine (0.1–0.8 g/100 g), threonine (0.2–0.8 g/100 g), methionine (0.02–0.3 g/100 g), tryptophan (0.04–0.6 g/100 g), and phenylalanine (0.4–8.7 g/100 g) (Adenekan et al., 2018; Athanas, 2022; Kuraz Abebe, 2022). The high level of leucine and lysine makes pigeon pea especially suitable for people with obesity, diabetes mellitus (Pedroso et al., 2015), and people who need more calcium such as athletes (Chromiak & Antonio, 2002).…”
Section: Nutritional Profile Of Pigeon Peamentioning
confidence: 99%
“…found that pigeon pea was surprisingly high in VC (569.2 mg/100 g) and β‐carotene (0.364 mg/100 g) contents amongst other 27 crops, which certainly contributed to the high antioxidant ability of pigeon pea (Ellong et al., 2015). For minerals, except phosphorus (127–367 mg/100 g) and potassium (552–1392 mg/100 g), pigeon pea is characterized by its richness in calcium (Ca; 16.3–200.9 mg/100 g) and magnesium (Mg; 68–183 mg/100 g) (Athanas, 2022; Kunyanga et al., 2013; Kuraz Abebe, 2022; Olalekan & Bosede, 2010; Rizvi et al., 2022).…”
Section: Nutritional Profile Of Pigeon Peamentioning
confidence: 99%
“…The species is used in animal (Neres et al., 2012) and human (Miano et al., 2020) food and also as a strategy to maintain soil sustainability (Teodoro et al., 2018). Abebe (2022) highlighted the potential use of guandu bean for human and animal food due to its high protein content and low production cost. In general, the protein content in guandu bean grains is 20%–22% (Venkata et al., 2019) and 23%–33% in dry matter (leaves and tender portions of stems) (Neres et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean ( Glycine max L.) has been regarded as one of the most important summer legume crops for human and animal diets worldwide (Adami and Leskovšek, 2021 ; Abebe, 2022 ), having served as an important source of dietary protein and oil for the past 20 years (Akmalovna, 2022 ). In addition, its consumption has outpaced its production.…”
Section: Introductionmentioning
confidence: 99%